DIAGNOSIS AND TREATMENT OF TICK-BORNE DISEASES OF PETS - Левицька, В. А.; Мушинський, А. Б. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
In recent years, there has been an increase in the number of tick-borne diseases around the world, especially borreliosis, rickettsiosis (anaplasmosis, ehrlichiosis), tick-borne encephalitis and others. Climate and environmental changes, migration (movement) of domestic animals lead to changes in the epizootiological situation regarding communicable diseases. The analysis of epizootological, clinical, laboratory data is carried out. The data of scientific researches concerning tick-borne diseases, namely borreliosis, ehrlichiosis, tick-borne encephalitis, louping-ill infection are generalized. In recent years, infectious and invasive animal diseases caused by viruses, bacteria and protozoa transmitted by ticks have become a new challenge in health and veterinary practice. Many such diseases are zoonoses and lead to disability and mortality in humans and animals. Ixodid ticks often attack animals and humans and are widespread throughout Europe, as well as being involved in the transmission of a large number of tick-borne diseases. Currently, one of the biggest threats is the pathogens of the complex Borrelia burgdorferi s. l., which belong to the spirochetes and affect various species of mammals and birds and are transmitted by ticks (Ixodes ricinus, Ixodes hexagonus and Ixodes persulcatus). The disease is of great epidemiological importance for human health. Diagnosis and treatment are insufficiently developed. Ehrlichia spp. are gramnegative, obligate intracellular bacteria from the family Anaplasmataceae. In Europe, Ehrlichia canis is the etiological agent of monocytic ehrlichiosis in dogs. The main host of E. canis is a dog (other dogs can serve as reservoir hosts); vector - Rhipicephalus sanguineus. Tick-borne encephalitis, as well as louping-ill infection, are diseases transmitted by Ixodid ticks and pose a danger to dogs, cats and other animals, as well as people in Europe. At present, all these diseases acquire important epizootological significance, as diagnosis and treatment are complicated. The main measure of disease prevention among dogs is the effective protection of animals from tick attack. Tick-borne diseases are a type of infectious and invasive diseases of animals and humans, the causative agents of which spread from one susceptible subject to another with the participation of blood-sucking arthropods. The most common and clinically significant diseases are: borreliosis, ehrlichiosis, tick-borne encephalitis and other. Systematic studies of zoonotic diseases have not been conducted in Ukraine. Systematic monitoring of pathogens and effective control of communicable diseases of animals are the basis for improving the epidemiological situation among the population.